KETIDAKPASTIAN HUKUM DALAM PENYELESAIAN SENGKETA BISNIS INTERNASIONAL MELALUI ARBITRASE INTERNASIONAL DI INDONESIA - Winata, Agung Sujati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
In business activities, one of the considerations for international business partners is the legal certainty of a country. This study aims to analyze the causes of legal uncertainty in settlement of international business disputes through international arbitration in Indonesia. This research is descriptive of the type of normative legal research. The data used to examine the issues under study include regulations related to legal certainty in settlement of disputes through international arbitration and secondary legal materials in the form of scientific works and the results of research by legal experts, especially those related to international arbitration. The approach used is a statutory approach, especially the AAPS Law. Data was collected through a literature study, then analyzed qualitatively. The findings of this study are that legal uncertainty in settlement of disputes through international arbitration occurs due to inconsistencies in implementing the provisions of the AAPS Law, particularly concerning the recognition and enforcement of international arbitral awards. In addition, there are no clear limits on violations of public order as a condition for international arbitral awards to be implemented in Indonesia